2002
DOI: 10.1051/0004-6361:20020772
|View full text |Cite
|
Sign up to set email alerts
|

Detection of solid ammonia, methanol, and methane with ISOPHOT

Abstract: Abstract. We report on a search for the NH 3 inversion band at 9.0 µm, the CH 4 band at 7.7 µm, and the CH 3 OH band at 9.7 µm in the spectra of 10 heavily obscured stellar objects taken with the spectrophotometer ISOPHOT-S aboard the Infrared Space Observatory (ISO). Four of them show indications of the NH 3 inversion band at 9.0 µm superimposed on the always strong silicate band. The results show that ammonia ice may be abundant in some cool and dense molecular circumstellar regions. The 9.7 µm band of solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 23 publications
(42 reference statements)
7
47
1
1
Order By: Relevance
“…The upper limit of the ratio of C 2 H 6 ice to CH 4 ice in NGC 7538 IRS 9 is considerably smaller than the ratio obtained in comet 153P/Ikeya-Zhang. The abundance of ethane ice to water ice in NGC 7538 IRS 9 is less than 0.4%, which is comparable to the value observed in the comet, and the relative abundance of methane ice to water ice in the interstellar medium (1%-2% at best) is slightly higher than the cometary value obtained here (Boudin et al 1998;Gü rtler et al 2002). If the upper limits of ethane ice in NGC 7538 IRS 9 are typical in the interstellar medium, there are two possible mechanisms for realizing these facts.…”
Section: Relative Abundance Of Ethane To Methane and Formation Conditsupporting
confidence: 58%
“…The upper limit of the ratio of C 2 H 6 ice to CH 4 ice in NGC 7538 IRS 9 is considerably smaller than the ratio obtained in comet 153P/Ikeya-Zhang. The abundance of ethane ice to water ice in NGC 7538 IRS 9 is less than 0.4%, which is comparable to the value observed in the comet, and the relative abundance of methane ice to water ice in the interstellar medium (1%-2% at best) is slightly higher than the cometary value obtained here (Boudin et al 1998;Gü rtler et al 2002). If the upper limits of ethane ice in NGC 7538 IRS 9 are typical in the interstellar medium, there are two possible mechanisms for realizing these facts.…”
Section: Relative Abundance Of Ethane To Methane and Formation Conditsupporting
confidence: 58%
“…It should be noted that the line of sight abundances of CH 3 OH and CO 2 is ∼5-10 times lower than the abundances found close to the protostellar sources due to the dominance of H 2 O ice in the cold outer regions (Gerakines et al 1999). It was recently shown that, contrary to earlier views (Gibb et al 2001;Gürtler et al 2002), most of the ammonia in IS ices is probably present in the form of the ammonium ion, NH + 4 , rather than as NH 3 (Taban et al 2003;Schutte & Khanna 2003). In this paper, however, NH 3 is used as a component of the starting ice mixture.…”
Section: Introductionmentioning
confidence: 77%
“…The Glass I system was originally considered a field star because Hα emission was not detected (Glass 1979), but then Feigelson & Kriss (1989) The silicate emission in Glass Ib is variable as well. This was first recognized by Gürtler et al (1999), with the 10 μm flux decreasing by a factor of 2 between 1996 February and 1997 July. Natta et al (2000) observed the system at an intermediate time between those observations in their study of silicate emission from YSOs.…”
Section: Emissionmentioning
confidence: 87%
“…If the shell expands on the order of 20-30 km s −1 , this peak transition from the 10 μm silicate to longer wavelengths occurs over the period of just a few years (Volk & Kwok 1989;Volk 1992). However, the silicate emission has been seen reported toward Glass Ib as early as 1996 February (Gürtler et al 1999). If the dust is in an expanding shell, the continuum would be expected to show stronger infrared excess as opposed to still being similar to Infrared Astronomical Satellite (IRAS) observations (see Figure 6).…”
Section: Planetary Nebulamentioning
confidence: 99%